Paradise : poems - Gibson, Stephen, 1948- (University of Arkansas Press, 2011)
Stephen Gibson is the author of three previous poetry collections, Frescoes (2009 poetry book prize from Lost Horse Press), Masaccio's Expulsion (2006 poetry book prize from MARGIE/IntuiT House), and Rorschach Art (Red Hen Press). He is a past Individual Artist Fellowship recipient from the State of Florida in both poetry and fiction.